Pre-Service Teachers Perception on The Use of Podcast - bhaskara, Alfin wahyu kunta (Jurnal Ilmiah Wahana Pendidikan, 2024)
People of all ages like listening to podcasts. They are a source of actual language with a varied spectrum of speakers, making them highly useful in language teaching in addition to being instructive and amusing. To maximize their potential as teaching resources, podcasts must be carefully investigated and evaluated from the viewpoint of language teachers. To do this, pre-service teachers who are evaluating podcasts as possible EFL teaching resources are monitored as both language learners and language teachers. This essay's main goal is to look into the opinions and attitudes of aspiring English instructors on the use of podcasts in EFL classes. This research employed a descriptive qualitative methodology. The findings indicate that pre-service teachers believe podcasts can aid in their English language acquisition. They both concur that podcasts are employed as a tool for English language acquisition.